Implementation of the Governor's Policy on Free Education in Improving the Quality of State Vocational High School Education in Banten Province, Indonesia - Imam Suyudi; Sudadio Sudadio; Asep Muhyidin (Jurnal Pendidikan Indonesia Gemilang, 2026)
Based on the constitutional mandate and the promulgation of Governor Regulation No. 52 of 2020, the policy of free education in the Banten Province eliminates the financial barriers of students in Public Senior High School, Public Vocational Senior High School, and Public Special Needs School with the goal of providing equal opportunities and human resource development. This study aimed to investigate the implementation of the policy and its implications for the quality of vocational high schools, which are significant in regional development and labor market integration. Data collection methods employed in the study were observations, in-depth interviews, and documentation using the qualitative descriptive approach. The researcher utilized government publications and foreign literature as sources of information for the study. The analysis of the data collected in the study was underpinned by the theory of policy implementation with emphasis on decentralized governance, administrative capacity, and regulatory clarity. The validity of the study was ensured through triangulation. The results indicate that inter-institutional collaboration, sufficient funding, and the existence of a cogent legal regime are essential for the successful implementation of policies. Although the dropout rates have reduced and access has increased, quality enhancement demands investments in infrastructure, leadership skills, monitoring, and teachers' competence. Further, the financial support must be supplemented with a system of accountability, quality control, and constant evaluation to ensure the effectiveness of the policies in the long term. In the decentralized education system in Banten, in developing countries, the link between equity-oriented funding and results-oriented governance ensures that enrollment is supplemented with significant improvements in learning outcomes and workforce readiness.